2018
DOI: 10.1029/2018ja025921
|View full text |Cite
|
Sign up to set email alerts
|

Multispacecraft Observations of Tailward Propagation of Transient Foreshock Perturbations to Midtail Magnetosheath

Abstract: We present three events from multiple spacecraft observations to show that a dayside transient foreshock perturbation associated with an interplanetary magnetic field directional discontinuity can propagate in the midtail magnetosheath and affect the magnetopause. In the first event, perturbations in density and flow were first observed in the dayside foreshock and later in the tail magnetosheath at X~À40 R E , a correlation suggests that the foreshock-originating perturbations propagated to the midtail. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 60 publications
5
20
0
Order By: Relevance
“…Around the same time at Point 3, the magnetopause movement, first outward then inward as shown in Figures 3b and 3c, causes the transient appearance of the magnetosphere, as indicated by the magnetic field strength and density changing to the magnetospheric values. The temporal profiles at Points 2 and 3 are qualitatively similar to the perturbations observed simultaneously by two satellites near the midtail magnetopause at x = −54 R E reported in Figure 8 of C. P. Wang, Liu, et al (2018). This supports that the perturbations associated with the second scenario described in section 1 can be strong enough to directly impact the midtail magnetopause.…”
Section: Simulation Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Around the same time at Point 3, the magnetopause movement, first outward then inward as shown in Figures 3b and 3c, causes the transient appearance of the magnetosphere, as indicated by the magnetic field strength and density changing to the magnetospheric values. The temporal profiles at Points 2 and 3 are qualitatively similar to the perturbations observed simultaneously by two satellites near the midtail magnetopause at x = −54 R E reported in Figure 8 of C. P. Wang, Liu, et al (2018). This supports that the perturbations associated with the second scenario described in section 1 can be strong enough to directly impact the midtail magnetopause.…”
Section: Simulation Resultssupporting
confidence: 79%
“…These newly generated magnetosheath perturbations thus propagate tailward while maintaining a good correspondence with the FB in the solar wind and the transmitted RD in the magnetosheath. This sequence, which represents the second scenario described in section 1, can qualitatively explain the tailward propagation of foreshock transient‐driven magnetosheath P d perturbations subsequently observed by two satellites at x = −27 and −50 R E reported in Figure 5 of C. P. Wang, Liu, et al (2018).…”
Section: Simulation Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Although foreshock transients are usually localized and transient, it has been reported that some foreshock transient‐driven geoeffects can be global. Recent study has shown that the foreshock transient perturbations are able to propagate to the midtail magnetosheath and disturb the magnetopause continuously (Wang, Liu, et al, 2018). HFAs are observed with global Pc3 ULF waves in the magnetosphere (Zhao et al, 2017) and substantial longitudinal propagation of ionospheric activities, which include traveling convection vortices (TCVs) and diffuse/discrete auroral brightening (Eastwood et al, 2008; Fillingim et al, 2011; Wang, Nishimura, Hietala, Lyons, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In previous observations, such perturbations were seen in the dayside region. Recent multipoint observations by Wang et al (2018) found that as the driver discontinuity of a foreshock transient convected tailward with the solar wind, the foreshock transient‐driven perturbations propagated with the discontinuity from the dayside magnetosheath to the midtail magnetosheath (X ~ −30 to −50 R E ), which caused local outward motion of the midtail magnetopause. Additionally, STEREO at X ~ −310 R E also observed HFA‐like perturbations in the far tail magnetosheath (Facskó et al, 2015).…”
Section: Introductionmentioning
confidence: 99%